(untitled) (Scientia Agricola, 2001)
The urease is the responsible enzyme for hidrolisis of urea into ammonia. The use of a urease source for the treatment of sugarcane bagasse with urea can improve the urea decomposition process into ammonia, improving the nutritious value of the material. The objective of this work was to evaluate the effect of the level of ground whole soybean as a urease source for sugarcane bagasse ammoniation through urea. Four levels of whole soybean (0, 2.5, 3.75 and 7.5% on dry matter basis), were added to sugarcane bagasse treated with 7.5% of urea (on dry matter basis) and stored during 96 days in plastic bags (50 L). A complete randomized design with four treatments and three replicates was used. Dry matter, crude protein and hemicellulose contents were not affected by urease levels, there was, however, a positive quadratic effect for in vitro dry matter disappearance and a negative linear effect for neutral detergent fiber disappearance. The use of 3.75% of whole soybean in the ammoniation through urea was beneficial for the improvement of the dry matter digestibility of sugarcane bagasse.